Research Note: The New Role of a Central Asian Diaspora - Vera Skvirskaja (The Copenhagen Journal of Asian Studies, 2022)
One of the common features of post-Soviet Central Asian diapora is its close connection to the homeland (the independent countries  of the former Soviet Central Asia) manifested in various economic ties, including investments into kinship networks and business ventures. This research note discusses the transnational Bukharan Jewish diaspora and its links to Uzbekistan that do not fit into this general pattern. Drawing on the history of Bukharan Jews as a ‘go-between’ minority at the time of Russia colonisation of Central Asia in the 19th and early 20th centuries, it investigates the ways in which this structural role has been actualised after the collapse  of the USSR and mass emigration of the Bukharan Jews from Central Asia. While the Bukharan Jewish diaspora do not seem to establish new economic lniks to Uzbekstan, the Bukharan Jewish community ogranisaitons strive to become a recognised player in the field of people’s diplomacy.